2021
DOI: 10.3233/jad-201105
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Bulbar MRI Hyperintensity in Anti-IgLON5 Disease with Serum-Restricted Antibodies: A Case Report and Systematic Review of Literature

Abstract: Background: Anti-IgLON5 disease is a rare neurodegenerative tauopathy that displays heterogeneity in clinical spectrum, disease course, cerebrospinal fluid (CSF) findings, and variable response to immunotherapy. Sleep disorders, bulbar dysfunction, and gait abnormalities are common presenting symptoms, and conventional brain MRI scanning is often unrevealing. Objective: To provide a comprehensive overview of the literature and to assess the frequency of symptoms, MRI findings, and treatment response in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The clinical spectrum of this disorder is still broadening, since the number of reported cases is still low, and cognitive decline as a symptom has been described in 40% of patients, even causing dementia (3). An early treatment with immunosuppressant or immunomodulatory drugs seems to be effective, but even with therapy the greater part of so far described patients suffered from chronic progression or remaining deficits (4,5). Regarding its low prevalence in the general population, only a few articles have addressed symptoms and the course of the anti-IgLON5 disease.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical spectrum of this disorder is still broadening, since the number of reported cases is still low, and cognitive decline as a symptom has been described in 40% of patients, even causing dementia (3). An early treatment with immunosuppressant or immunomodulatory drugs seems to be effective, but even with therapy the greater part of so far described patients suffered from chronic progression or remaining deficits (4,5). Regarding its low prevalence in the general population, only a few articles have addressed symptoms and the course of the anti-IgLON5 disease.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has been consistently reported that about 10% of anti-IgLON5 disease patients test negative for anti-IgLON5 IgG in CSF [e.g. (38,39)]. These probably correspond to those with low CSF levels in our cohort when using flow cytometry.…”
Section: Discussionmentioning
confidence: 61%
“…Although some patients with IgLON5 antibodies were responsive to immunotherapy, consistent with most other forms of neuronal cell‐surface autoantibody‐mediated diseases, 22,23 patients with improvement in symptoms still require long‐term follow‐up because symptoms may worsen and patients may die suddenly 1,14,24,25 . Grüter et al 26 .…”
Section: Discussionmentioning
confidence: 91%
“…Although some patients with IgLON5 antibodies were responsive to immunotherapy, consistent with most other forms of neuronal cell-surface autoantibody-mediated diseases, 22,23 patients with improvement in symptoms still require long-term follow-up because symptoms may worsen and patients may die suddenly. 1,14,24,25 Grüter et al 26 found that first-line immunotherapy of relapselike acute-to-subacute exacerbation episodes resulted in improvement in 41% of patients and early immunotherapy (before advanced neurodegeneration) was associated with a better long-term clinical outcome. In cultures of hippocampal neurons, antibodies of patients caused a decrease in cell-surface IgLON5 clusters that was not reversed after IgLON5 antibodies were removed from the media, indicating an irreversible antibody-mediated internalization of surface IgLON5 in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%